Aero-thermal-elastic Coupled Simulations of An Air-cooled Turbine with an FDM solver. (July 2020) - Guo, Zhaoyuan; Wang, Qiang; Dong, Ping; Jiang, Yuting
Abstract: The aero-thermal-elastic coupled simulations of an air-cooled turbine vane were carried out by a developed coupled solver, HIT3D, employing the finite difference method. The pressure on the vane surface and the temperature in the solid vane were obtained by the coupled heat transfer simulation, then the single-way aero-elastic and thermal-elastic analysis on the turbine vane were performed. It shows that the predicted profile temperature employing the transition model agrees well with the measured one, the blade deformation caused by aerodynamic force is negligible, and that the greater thermal deformation and thermal stress locate at the blade leading edge pressure side and at the blade trailing edge, as the result of the strong temperature gradient and the constraint at the vane endwalls.